Triple Higgs production at hadron colliders at NNLO in QCD - de Florian, Daniel Enrique (2020)
In this work we analyse the triple Higgs boson production cross section at hadron colliders via gluon fusion, and present for the first time the full set of QCD NNLO corrections in the heavy top limit. In order to account for finite top mass effects we perform two different reweighting procedures, and study the dependence of the result on the choice of the approximation. Combining the most accurate predictions available to date, we present the following result for the total NNLO cross section for triple Higgs boson production at a 100 TeV collider: σNNLO=5.56−6%+5%± 20% fb, where the first uncertainty is an estimate for higher order effects from scale variations, while the last one is an estimate for the missing finite top mass effects.